Supply Chain Coordination Competency and Firm Performance: An Empirical Study - Rajendra Kumar Shukla; Dixit Garg; Ashish Agarwal (International Journal of Supply Chain Management, 2013)
Thispaper presents a model to conduct an empirical study in Indian industries toimprove the performance of their supply chain. The present research focuses onvarious variables that affect coordination and performance of supply chain of amanufacturing company. In a survey, variables helping in improving coordinationand performance of the supply chain have been gauged. With the help of factoranalysis, top priority variables have been identified. The findings show that contracts, standardizationof rules, joint cost minimization, risk and reward sharing and uses ofelectronic data interchange (EDI) have a significant influence on the coordination.Learning and growth, better product quality, reduced customer complaints, profitsmargin and customer service level are emerged as top level performance indicatorsof manufacturing organizations. Further, a framework is suggested, thatincludes the relationship between top priority variables of supply chaincoordination and firm performance. Keywords: Supply chain management, Supplychain coordination, coordination mechanisms, Firm performance, Factor analysis